Optimal control policies for assemble-to-order systems with commitment lead time. (2nd December 2019) - Ahmadi, Taher; Atan, Zumbul; de Kok, Ton; Adan, Ivo
Abstract: In this article, we study a preorder strategy which requires customers to place orders ahead of their actual need. We characterize the preorder strategy by a commitment lead time. We define the commitment lead time as the time that elapses between the moment an order is communicated by the customer and the moment the order must be delivered to the customer. We investigate the value of using this preorder strategy in managing assemble-to-order systems. For this purpose, we consider a manufacturer, who operates an assemble-to-order system with two components and a single end product. The manufacturer uses continuous-review base-stock policies for replenishing component inventories. Customer demand occurs for the end product only and unsatisfied customer demands are backordered. Since customers provide advance demand information by preordering, they receive a bonus. We refer to this bonus from the manufacturer's perspective as a commitment cost. We determine the optimal component base-stock levels and the optimal length of the commitment lead time, which minimize the sum of long-run average component inventory holding, backordering and commitment costs. We find that the optimal commitment lead time is either zero or equals the replenishment lead time of one of the components. When the optimal commitment lead time is zero, the preorder strategy is not beneficial and the optimal control strategy for both components is buy-to-stock. When the optimal commitment lead time equals the lead time of the component with the shorter lead time, the optimal control strategy for this component is buy-to-order and it is buy-to-stock for the other component. On the other hand, when the optimal commitment lead time equals the lead time of the component with the longer lead time, the optimal control strategy is the buy-to-order strategy for both components. We find the unit commitment cost thresholds which determine the conditions under which one of these three cases hold.